NATIONAL-HISTORICAL CONTEXTUAL ASPECTS OF DEVELOPING NATIONAL EDUCATION AND MORAL IMMUNITY CONCEPTS IN STUDENTS (Universal International Scientific Journal, 2026)
The article discusses the issues of ensuring the continuity of education at all stages of education, the role of the family and the community in this regard. Some aspects of this continuity system are analyzed, and opinions and proposals for further improvement are expressed. Special emphasis is placed on the development of universal human values. Examples and ideas from the works of national and foreign scientists and writers are given.
Keywords: New Uzbekistan, preschool education, school education, higher education, university, humanism